MEMBANGUN CUSTOMER VALUE PADA INDUSTRI PARIWISATA BALI (Suatu Pendekatan Kualitas Pelayanan, Citra, Kepuasan dan Loyalitas Wisatawan): MEMBANGUN CUSTOMER VALUE PADA INDUSTRI PARIWISATA BALI (Suatu Pendekatan Kualitas Pelayanan, Citra, Kepuasan dan Loyalitas Wisatawan) - Ni Nyoman Seri Astini; Ida Bagus Gede Udiyana (Forum Manajemen, 2009)
This study analyze about developing the customer value on the industry of tourism bali. The aim of this study is to discover the role and the relation among the customer value and the quality of service, the image, satisfaction and tourist loyality. The methodology of this study consist of library research, all the data source are secondary data such as books, journals, and newspapers.